Islamic-Based Inclusive School Management Strategies - Baidowi, Ach.; Dzulhasnan, Ainul Haninah; Kusmawati, Ati; Athiyallah, Arina (Al Irsyad: Jurnal Studi Islam, 2025)
Inclusive schools integrate all students regardless of their differences, requiring curriculum adjustments, teacher training, and collaborative leadership grounded in Islamic values to create a fair and inclusive learning environment. This study aims to identify effective strategies and analyze the implementation of Islamic values in the management of inclusive schools to establish a just and holistic educational setting. The research was conducted through a literature study employing a Systematic Literature Review (SLR) approach, involving data processing steps such as topic determination, data searching, data screening, and data presentation. The findings indicate that the integration of Islamic values into inclusive school management positively impacts the creation of an educational environment that is equitable, adaptive, and spiritual. The curriculum is tailored to the individual needs of students with special needs, while teacher competency strengthening focuses on the application of inclusive learning strategies based on Islamic values. School leadership emphasizes ethical principles and spirituality in decision-making processes. Additionally, assistive technology support, disability-friendly infrastructure, and active community and parental involvement reinforce the implementation of inclusion. This holistic approach shapes a contextual, equitable, and sustainable Islamic-based inclusive school model. Conclusion: Islamic-based inclusive education requires an adaptive curriculum, competent teachers, disability-friendly infrastructure, and inclusive policies supported by Islamic values and sustained cross-sector collaboration.